2022
DOI: 10.3390/c8030043
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Refractive Index Indicates the Concurrent Role of the Bio-Structuration Process in the Comparison with the Nano-Structuration One

Abstract: It should be remarked that the basic knowledge collected from complicated area of the structuration process of the organic materials, including the liquid crystal (LC) ones, useful for the optoelectronics and biomedicine, requires extending the types of the novel matrix model materials and the class of the dopants, which can change the spectral and photorefractive features of the matrixes with good advantage. In the current paper the effect of the introduction of the bio-objects (based on DNA) and of the nano-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…A good fundamental review of the advances in biophotonics in the 21st century was made in [38]. Moreover, the tendency to replace the nanostructuration doping with the bio-structuring one was established and explained in [39][40][41][42][43]. It was shown that bio-object-doped materials reveal the nonlinear optical coefficients close to those for the nano-object-sensitized ones that permit us to conclude the following main idea: the existence of an innovative tendency to use the non-toxic bio-objects instead the nano-object ones to optimize the organic photorefractivity [39,40].…”
Section: Type Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A good fundamental review of the advances in biophotonics in the 21st century was made in [38]. Moreover, the tendency to replace the nanostructuration doping with the bio-structuring one was established and explained in [39][40][41][42][43]. It was shown that bio-object-doped materials reveal the nonlinear optical coefficients close to those for the nano-object-sensitized ones that permit us to conclude the following main idea: the existence of an innovative tendency to use the non-toxic bio-objects instead the nano-object ones to optimize the organic photorefractivity [39,40].…”
Section: Type Of Materialsmentioning
confidence: 99%
“…Moreover, the tendency to replace the nanostructuration doping with the bio-structuring one was established and explained in [39][40][41][42][43]. It was shown that bio-object-doped materials reveal the nonlinear optical coefficients close to those for the nano-object-sensitized ones that permit us to conclude the following main idea: the existence of an innovative tendency to use the non-toxic bio-objects instead the nano-object ones to optimize the organic photorefractivity [39,40]. The nonlinear susceptibility tuning in a functionalized DNA system was established in [41]; the rotation of the polarization plane of light via use of DNA-based structures for liquid crystal doping to apply in innovative medical devices was shown in [42]; and nano-and bio-particle-assisted optical bio-imaging was proposed in [43].…”
Section: Type Of Materialsmentioning
confidence: 99%